Role of the admission muscle injury indicators in early coagulopathy, inflammation and acute kidney injury in patients with severe multiple injuries - Liuquan Mu; Haideng Song; Mengdi Jin; Kaige Li; Yushan Guo; Nan Jiang (World Journal of Emergency Surgery)
Abstract Backgrounds Coagulopathy, inflammation and organ failure are common complications in trauma patients. This study aimed to explore the possible role of muscle injury indicators in early coagulopathy, systemic inflammatory response syndrome (SIRS), and acute kidney injury (AKI) in patients with severe multiple trauma. Methods A retrospective analysis was performed using trauma center patient data from 2020 to 2023. The incidence of coagulopathy, SIRS and AKI in patients with multiple injuries were assessed. The relationship between Myoglobin, creatine kinase (CK), lactate dehydrogenase (LDH) and trauma severity was investigated, and the influence of these three muscle injury indicators on patient adverse outcomes was analyzed. Results A total of 312 patients with severe multiple injuries were included in this study, with an average age of 51.7 and a median Injury Severity Score (ISS) of 22.5. Among them, 115 patients developed coagulopathy, 169 patients developed SIRS, 26 patients developed AKI, and 11 patients died during hospitalization. We found that Myoglobin (r = 0.225, P < 0.001), CK (r = 0.204, P < 0.001), LDH (r = 0.175, P = 0.002) were positively correlated with ISS. Myoglobin is an independent risk factor for coagulopathy (OR = 1.90, 95%CI: 1.45–2.49), SIRS (OR = 1.41, 95%CI: 1.10–1.79), and AKI (OR = 4.17, 95%CI: 2.19–7.95). CK is an independent risk factor for coagulopathy (OR = 1.30, 95%CI: 1.00-1.67), while LDH is an independent risk factor for SIRS (OR = 1.49, 95%CI: 1.17–1.89) and AKI (OR = 2.30, 95%CI: 1.43–3.69). Especially for AKI, Myoglobin had a good predictive effect (AUC = 0.804, 95%CI:0.716–0.891). The best cut-off value is when the Myoglobin value is 931.11 µg/L, at which point the sensitivity is 61.53% and the specificity is 87.41%. Conclusions The admission muscle injury index can predict trauma complications such as AKI, early coagulation disease, and SIRS, especially AKI. Compared to CK and LDH, admission myoglobin can predict complications remarkably, even better than ISS, especially AKI. Routine testing of muscle injury indicators upon admission is meaningful and can help physicians identify and prevent the occurrence of complications.